Running the Gauntlet: Assessing the Threats to Vertical Migrators - Robison, Bruce H.; Sherlock, Rob E.; Reisenbichler, Kim R.; McGill, Paul R. (Frontiers in Marine Science, 2020)
Diel vertical migrations by zooplankton and nekton are driven by the selective advantage of avoiding visually cued predators near the surface during the hours of daylight. And just as there is a second set of predators that occupy the migrators’ dark daytime depths, there is also a diverse suite of predators that comprise a gauntlet of threats during the migrations. Here we examine these migrations from the perspective of the migrators, to enumerate the kinds of predatory threats they face and to assess the threat potential of various predator types. The study is based on thousands of hours of in situ observations and measurements of the mesopelagic community in Monterey Bay, California, conducted chiefly by remotely operated vehicles. We provide accounts of some predator/prey interactions, and we introduce a means to calculate the threat potential of specific predators, based on MBARI’s long-term time-series of quantitative video surveys.